Papillary cystadenoma of the epididymis - Olga Lopez; Hisham F. Bahmad; Ruben Delgado; Billy H. Cordon; Robert Poppiti; Lydia Howard (Autopsy and Case Reports, 2022)
Background: Papillary cystadenoma is a rare benign neoplasm of the epididymis. It may occur sporadically or in association with von Hippel-Lindau disease (VHLD). Papillary cystadenoma of the epididymis (PCE) is a benign mimic of metastatic clear cell renal cell carcinoma (CCRCC) given their histologic similarities.Case presentation: Herein, we present the case of a 40-year-old man with a four-year history of microhematuria and a recently detected right paratesticular mass. A testicular sonogram revealed a hypoechoic, hypervascular solid mass in the right epididymal head treated by surgical excision. Histopathological examination demonstrated a 1.1 cm papillary cystadenoma of the epididymis. Genetic testing performed later showed no signs of VHLD. However, heterozygous mutations in three genes - CASR, POT1, and RAD51D - were found which have never been reported in PCE before.Conclusions: Papillary cystadenoma of the epididymis should always be considered in the differential diagnosis of epididymal lesions, especially those that are cystic. The mainstay of treatment remains surgical excision, which provides an excellent prognosis.